PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM DUNIA PENDIDIKAN - Yuda Pebrian; Muhamad Fathi Farhat (Abdi Jurnal Publikasi, 2023)
The utilization of artificial intelligence (AI) technology has become an urgent need in improving the quality of education. This research aims to explain the implementation and impact of AI utilization in education and to make a positive contribution to community development. The research methods used are action research and case studies to gain an in-depth understanding of the effectiveness of using AI in improving the quality of learning.